2018
DOI: 10.1002/ird.2275
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Climate Change: Impact of Capacity Building, India

Abstract: Climate change adversely affects the determinants of agriculture. Adaptation serves as an important strategy to reduce the adverse effects of climate change (variability) and vulnerability of the people. Adaptation through an innovation programme was implemented for 4 years during 2012–2016 to improve the adaptive capacity in agriculture and the water sectors through capacity building and implementation in the Krishna River Basin, India. Primary data were collected from 178 farm households of the Nagarjuna Sag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Expanding smart AWM at scale has been an issue, and awareness and capacity building are the key constraints in improving adaptive capacity to scaling out resilient interventions. An innovative approach to capacity building under the ClimaAdapt Project was implemented from 2012 to 2016 to improve the adaptive capacity of stakeholders and farmers' groups in the Krishna River basin, India (Kakumanu et al, 2019). The study was taken up under the Nagarjuna Sagar Project in the selected command areas in the Nalgonda District of Telangana and the Guntur District of Andhra Pradesh, covering 178 farmers.…”
Section: The Way Forward: Scaling Up Awm For Resilient Agriculturementioning
confidence: 99%
“…Expanding smart AWM at scale has been an issue, and awareness and capacity building are the key constraints in improving adaptive capacity to scaling out resilient interventions. An innovative approach to capacity building under the ClimaAdapt Project was implemented from 2012 to 2016 to improve the adaptive capacity of stakeholders and farmers' groups in the Krishna River basin, India (Kakumanu et al, 2019). The study was taken up under the Nagarjuna Sagar Project in the selected command areas in the Nalgonda District of Telangana and the Guntur District of Andhra Pradesh, covering 178 farmers.…”
Section: The Way Forward: Scaling Up Awm For Resilient Agriculturementioning
confidence: 99%
“…Adopting paddy cultivation practices like alternate wetting and drying (AWD), direct seeded rice (DSR) and system of rice intensification (SRI) can increase productivity by 35-40% (Deelstra et al, 2018;Kakumanu et al, 2018) depending on location. SRI provided a world record rice yield of 21.16 tons/ha (Kassam & Brammer, 2013) in Bihar.…”
Section: In Non-energy Matters: Indian Agriculturementioning
confidence: 99%
“…Government has started providing fieldspecific data to the farmers through mobiles or smart phones for better decision making related to amount of input use. But wide-scale scaling up of CSA in India needs data-driven technology generation process in Indian NARS (National Agricultural Research System) (Rao, 2018) so as to facilitate assimilation of field-specific Note Compiled by authors using the following sources: a (Kakumanu et al, 2018;Deelstra et al, 2018), b (Pathak et al, 2014), c (Basak, 2016)-reported for optical sensors, *Site-specific N-use; d (Chan et al, 2017); e (Groot et al, 2019)-reported emission intensity data, conveying data-driven agronomic knowledge to farmers and government extension agents for proper decision making. For this to be effective, joint participation of Government and private sectors plays pivotal role.…”
Section: In Non-energy Matters: Indian Agriculturementioning
confidence: 99%
“…The implementation of autonomous adaptation reduces the negative impacts of climate change. For example, improved irrigation systems increased rice yields in three cropping systems (direct-seeded, rice intensification system, and alternate wetting and drying) in India by 0.96, 0.93, and 0.77 tonnes/ha, and increased farmers income by 169 USD/ha (Kakumanu et al, 2019). Similarly, adjusting the rice cropping system increased production by 10 to 20% per hectare, while for annual crops, there was an increase in production by 8% per hectare (Kawasaki, 2018).…”
Section: Introductionmentioning
confidence: 99%